2004
DOI: 10.1212/01.wnl.0000140497.85952.fa
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal motor neuropathy

Abstract: Long-term IV immunoglobulin therapy improves muscle strength and functional disability, decreases the number of conduction blocks and the extent of axonal degeneration, and promotes reinnervation. These findings differ from previous reports of deterioration in neurophysiologic outcome measures. Comparison of the IV immunoglobulin regimen in those reports and this study shows that the authors' patients were treated with significantly higher IV immunoglobulin maintenance doses. These findings have implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
4
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 29 publications
6
94
4
6
Order By: Relevance
“…It is notable that dosing remained constant or was only slightly changed in the majority of patients over the course of 1 year. Notably, authors of a retrospective study found reliably good shortterm response to IVIG, but declining effectiveness in long-term follow up of patients [Léger et al 2008], that was confirmed by other studies [Van Den BergVos et al 2002;Terenghi et al 2004], while in another study their IgG effectiveness persisted [Vucic et al 2004]. In our study, IgG treatment was stopped in only one patient who did not have a clinical benefit from the treatment.…”
Section: Treatmentsupporting
confidence: 87%
“…It is notable that dosing remained constant or was only slightly changed in the majority of patients over the course of 1 year. Notably, authors of a retrospective study found reliably good shortterm response to IVIG, but declining effectiveness in long-term follow up of patients [Léger et al 2008], that was confirmed by other studies [Van Den BergVos et al 2002;Terenghi et al 2004], while in another study their IgG effectiveness persisted [Vucic et al 2004]. In our study, IgG treatment was stopped in only one patient who did not have a clinical benefit from the treatment.…”
Section: Treatmentsupporting
confidence: 87%
“…Elevated anti-ganglioside GM1 antibodies and definite conduction block have been shown to be correlated with a favourable response to IVIg (class IV evidence) (EFNS task force, 2008). However, in one retrospective study, treatment with higher than normal maintenance doses of IVIg (1.6-2.0 g/kg given over 4-5 days) promoted re-innervation, decreased the number of conduction blocks and prevented axonal degeneration in 10 MMN patients for up to 12 years (Vucic et al, 2004). Recommendations: -As there is no other treatment of proven benefit, the recommendation is to use IVIg (2 g/kg in 2-5 days) as a first-line treatment (level A).…”
Section: Intravenous Immunoglobulins In Neurological Diseases: Establmentioning
confidence: 98%
“…This decline started after 3-7 years (mean 4.8 years) of therapy and correlated with a reduction of distal compound muscle action potential amplitudes. However, another study reported significant and sustained improvement in muscle strength (assessed byMRC score in 8 muscle groups) [81], disability (assessed by Modified Rankin Score), CB, and signs of axonal degeneration on electrophysiological studies in 10 patients with MMN, with a follow-up of 3.5-12.0 years (mean 7.3 years). The authors concluded that long-term IVIG therapy improved muscle strength and functional disability, decreased the number of CBs and the extent of axonal degeneration, and promoted reinnervation.…”
Section: Ivigmentioning
confidence: 99%